Increased Yield of PCR Products by Addition of T4 Gene 32 Protein to the SMART™ PCR cDNA Synthesis System. (July 2001) - Villalva, C.; Touriol, C.; Seurat, P.; Trempat, P.; Delsol, G.; Brousset, P.
Under certain conditions, T4 gene 32 protein is known to increase the efficiency of different enzymes, such as Taq DNA polymerase, reverse transcriptase, and telomerase. In this study, we compared the efficiency of the SMART™ PCR cDNA synthesis kit with and without the T4 gene 32 protein. The use of this cDNA synthesis procedure, in combination with T4 gene 32 protein, increases the yield of RT-PCR products from approximately 90% to 150%. This effect is even observed for long mRNA templates and low concentrations of total RNA (25 ng). Therefore, we suggest the addition of T4 gene 32 protein in the RT-PCR mixture to increase the efficiency of cDNA synthesis, particularly in cases when low amounts of tissue are used.